If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -1x = 13 Solving 3a + -1x = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'x' to each side of the equation. 3a + -1x + x = 13 + x Combine like terms: -1x + x = 0 3a + 0 = 13 + x 3a = 13 + x Divide each side by '3'. a = 4.333333333 + 0.3333333333x Simplifying a = 4.333333333 + 0.3333333333x
| -16-5x=-6x+6 | | (3+2i)(4-2i)= | | -9(4b+1)+(37b-5)= | | 4(2y+1)=2(12y) | | 3*(x-2)-(x-5)=13 | | 0.75(h+4)=13.5 | | 11X+3=3X+35 | | x^2-9x+6=6 | | H(x)=4x^2+2x-5 | | 7+8=16 | | 2x^3+9x^2-7x+1=0 | | -1=0(3)+b | | 75-3x=5-10x | | (4y^2+9)(16y^2+.25)=0 | | 3x=-y+140 | | 2x^2+x+y+2y^2+2x+5-2x^2+y^2-7= | | 5*(2x-1)+(3x-32)=67 | | 2x+11=-17-5x | | 2=.66(-3)+b | | 5a-5whena=4 | | 2t^2+13t=7 | | 0.75(h+4)=7 | | 12x+2=10+4x | | 3=3(-2)+b | | 3x+5x-4=6x+5 | | 3(.75m+10)+2.50m-15=2(1.75m+12.50)-.75+4 | | 4=-0.5(-2)+b | | 3(3x-85)=4x | | 6+42x=21x+24 | | 11-22x= | | 3*(2x-1)+(3x-32)=67 | | -x^2-49=0 |